Analisis Penentuan Harga Sapi dalam Tradisi Marosok Ditinjau dari Perspektif Etika Bisnis Syariah di Pasar Muaro Paneh, Kecamatan Bukik Sundi, Kabupaten Solok - Nabila Hanania; Gusril Basir (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2024)
This research aims to find out what the description of cattle buying and selling transactions using the marosok system is in the Muaro Paneh market, and what is the perspective of sharia business ethich in buying and selling cattle using the marosok system in the Muaro Paneh market. This research uses qualitative methods with interviews and observations with cattle sellers at the Muaro Paneh market. The research results show that. Description of cattle buying and selling transactions using the marosok system are carried out only on Mondays from dawn to dusk. The cattle seller there always carries a cloth or sarong on his shoulder. The seller’s way of determining the price is by touching the buyer’s hand, and when bidding the buyer also touches the seller’s hand using the code of his fingers. Where the index finger can be worth hubdreds of thousands, one million, up to ten million rupiah. The perspective of sharia business ethich in buying and selling cattle using the marosok system at MuaroPaneh market is in accordance with the principles of sharia business ethics such as customer satisfacarion, fairness and trust in the process of buying and selling livestock.